Cytotoxic Effect of Tilia dasystyla and Polygonatum orientale Desf Extracts on AGS and SKOV-3 Cancer Cell Lines: Effect of Tilia dasystyla and Polygonatum orientale Desf on AGS and SKOV-3 Cancer - Zarringhalami, Roshanak; Hanachi, Parichehr; Ramezani Tamijani, Reihaneh (Iranian Journal of Pharmaceutical Sciences, 2020)
Nowadays medicinal plants have been considered as the complementary medicine in cancer treatment by researchers. Some plants possess chemical compounds which are able to inhibit the growth of cancer cells or even eliminate them through apoptosis or necrosis. In current study anticancer effect of Tilia dasystyla and Polygonatum orientale Desf extracts on AGS and SKOV-3 cancer cell lines were investigated. The cytotoxic effect of Tilia dasystyla and Polygonatum orientale Desf extracts on AGS and SKOV-3 has not been reported so far. Cancer cell lines were treated with different concentrations (100-5000 μg/ml) of T. dasystyla and P. orientale Desf methanol extracts for 24, 48, 72 hours. Cell viability of AGS and SKOV-3 cancer cells were evaluated by MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide) method. Results of the study indicate that, extracts of T. dasystyla and P. orientale Desf showed cytotoxic effect on AGS and SKOV-3 cancer cell lines. The lowest IC50 value of AGS and SKOV-3 cell lines was about 1.02 ± 0.01 mg /ml and 1.14 ± 0.17 mg / ml respectively. T. dasystyla and P. orientale Desf extracts showed cytotoxic effect on AGS and SKOV-3 cancer cell lines in time- and dose-dependent manner. Full potential of the extracts, as an option for cancer treatment, is yet to be determined by further studies on animal models and subsequent trials.